(untitled) (Élisée - Revista de Geografia da UEG, 2021)
The environmental perception can be understood as the awareness of human being, so that, when observing the environment in which he/she is inserted, he/she learns to protect and care for it in the best possible way. This becomes one of the main challenges for public managers, whose confrontation imposes the need to develop popular housing programs that consider in their framework, in addition to residences, the creation and maintenance of healthy environments. In this context, the present study intends to identify the environmental perception of the residents of Nova Ituiutaba I and III allotments, in the city of Ituiutaba, Minas Gerais, Brazil. For this purpose, a bibliographic review on the subject was elaborated, in addition to the application of semi-structured questionnaires for the residents of the investigated places. Data analysis showed that the Nova Ituiutaba I and III are located in a peripheral and discontinuous area of ​​the municipality largely composed of women and people over 36 years old. With regard to environmental perception, almost twice as many residents are not satisfied with the new habitation; however, they consider themselves happy, since living in a new residence symbolizes the dream of becoming proprietors of their own homes, in addition to the tranquility of the place and conviviality with the neighborhood.